2017
DOI: 10.2196/jmir.7108
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the General Data Protection Regulation on Medical Research

Abstract: BackgroundThe enactment of the General Data Protection Regulation (GDPR) will impact on European data science. Particular concerns relating to consent requirements that would severely restrict medical data research have been raised.ObjectiveOur objective is to explain the changes in data protection laws that apply to medical research and to discuss their potential impact.MethodsAnalysis of ethicolegal requirements imposed by the GDPR.ResultsThe GDPR makes the classification of pseudonymised data as personal da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(75 citation statements)
references
References 15 publications
(13 reference statements)
0
67
0
5
Order By: Relevance
“…Once an app has been optimized to maximize patient empowerment, several additional barriers need to be addressed in order to obtain full adoption of mHealth tools in clinical practice. Mobile apps collecting personal data have to comply with privacy regulations—General Data Protection Regulation (GDPR)—as well as with local laws. Strikingly, an analysis performed in 2014 showed that 30.5% of mobile health apps have included a privacy policy document and most require a high level of literacy .…”
Section: Discussionmentioning
confidence: 99%
“…Once an app has been optimized to maximize patient empowerment, several additional barriers need to be addressed in order to obtain full adoption of mHealth tools in clinical practice. Mobile apps collecting personal data have to comply with privacy regulations—General Data Protection Regulation (GDPR)—as well as with local laws. Strikingly, an analysis performed in 2014 showed that 30.5% of mobile health apps have included a privacy policy document and most require a high level of literacy .…”
Section: Discussionmentioning
confidence: 99%
“…Our findings show that dfDNC (RQ2) enhanced the care management of the digital literate care recipients, the feelings of safety among informal caregivers, and efficiency of organization by the formal caregivers, which are all basic ingredients of good quality of care [20]. Before actually using an e-tool, it is important to (RQ3) consider the several barriers and facilitators of success when implementing it into homecare organizations, such as anticipating on changes in data protection legislation [21]. Finally, digital networked communication may enhance the linkages in the triangle of client, informal caregiver and professional caregiver, and increase peace of mind amongst all users.…”
Section: To Concludementioning
confidence: 94%
“…The General Data Protection Regulation aims at increasing individuals’ control of personal data, including research data, and is expected to place higher demands on biomedical researchers in European countries with regard to data access. The Regulation states, for instance, that research participants should ‘receive their information in an appropriate form without hindrance’ to improve data portability 31. In practice, however, it will not always be easy for research groups to provide research participants with individual research data, as it may require effort to present data ‘in an appropriate form’.…”
Section: Other Reasons To Disclose Ad Biomarkersmentioning
confidence: 99%